2022-RA-816-ESGO The impact of the new RCOG 2019 curriculum and COVID 19 pandemic on gynaecological training amongst the specialist trainees in the United Kingdom: a prospective study. (20th October 2022) - Barakat, Anas; Ismail, Aemn; Chattopadhyay, Supratik
Abstract : Introduction/Background: The Royal College of Obstetricians and Gynaecologists (RCOG) introduced a new curriculum in 2019, where a new portfolio was implemented by all obstetrics and gynaecology trainees across the UK. Four professional identities replaced nineteen modules. Furthermore, the National Health Service was hit by the COVID 19 pandemic in 2020. Our survey aims to find how the new RCOG curriculum and COVID 19 pandemic affected gynaecological training amongst specialist trainees in the UK. Methodology: A cross sectional study was conducted using the University of Leicester online survey platform involving the RCOG trainees in the UK from the 1st of June 2021 to the 1st of October 2021. The survey was divided into two main categories: 1) new RCOG curriculum and gynaecology training, 2) COVID 19 pandemic and gynaecology training. Results: We received replies from 10% of trainees. The quality of gynaecology training under the new RCOG curriculum was described as less than good in 75.6% of respondents ( figure 1 ). However, it was observed that the subspecialty trainees were the most satisfied trainees, with 66.7% describing training as good to excellent.The COVID 19 pandemic adversely affected all aspects of gynaecology training. Benign gynaecology, subfertility, urogynaecology, and gynaeoncology modules training were affected in 94.0%, 85.1%, 89.7%, and 83.5% of trainees, respectively ( table 1 ). During the pandemic, gynaecology teaching was affected in 84.9% of trainees, redeployment occurred in 11.8% of trainees, and 16% suffered adverse ARCP outcomes. Conclusion: Our survey reveals that the new RCOG curriculum and COVID 19 pandemic have simultaneously compromised the gynaecology training amongst the UK trainees. RCOG and GMC-led more exhaustive survey would be welcomed to corporate our findings and take necessary actions. Gynaecology training amongst current trainees should be of the highest quality to optimize patient care in line with the professional skills recommended by the GMC.